Sentence Adverbials and Evidentiality - Hirschová, Milada (Research in Language, 2013)
The paper deals with expressions of evidence (originating in perception, inference or reported information) and their role in sentence/utterance pragmatic modification. It concentrates on the role of the so-called sentence adverbials, showing them as scoping / focussing elements the main function of which is a/ to mark focus of an utterance b/ to support speaker´s reasoning. Formal properties of evidential expressions are dissimlar to that point that they cannot be comprised into a unified category.